ANALISIS PUSTAKA MENGENAI DAMPAK PENGGUNAAN APLIKASI TIKTOK OLEH SISWA KELAS TINGGI SEKOLAH DASAR TERHADAP PERILAKU SOSIAL - Wianda Vinka Virgie; Tunjungsari Sekaringtyas; Endang Wahyudiana (STKIP Subang, 2025)
This study aims to examine various sources of literature that discuss the use of the TikTok application and its relationship to the social behavior of elementary school students, especially at the upper grade level. The approach used is a literature study, with data collection sourced from scientific journals, articles, books, and previous research results. The findings of the study indicate that the use of TikTok has two sides: providing benefits such as encouraging creativity and the ability to express oneself, but also causing risks such as addiction, reduced social empathy, and the emergence of consumptive behavior. Based on this, this study recommends the need for active involvement of parents and teachers in guiding children's use of social media.